2021
DOI: 10.1016/j.lana.2021.100069
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and Other Pandemic-related Predictors of Prospective Changes in Psychological Distress

Abstract: Background Numerous studies have documented mental health challenges during the COVID-19 pandemic. Few studies included pre-pandemic levels of mental health or were comprehensive in assessing factors likely associated with longer-term mental health impacts. Methods Analyses used prospective data from a subset of participants in the nationwide Cancer Prevention Study-3 (CPS-3) United States cohort (N=2,359; 1,534 women; 825 men) who completed surveys in 2018 and during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
(46 reference statements)
0
16
0
2
Order By: Relevance
“…The rise in the mental health needs of children and adolescents is steadily increasing. The COVID-19 pandemic, and especially its consequences, increased public awareness to mental health needs [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rise in the mental health needs of children and adolescents is steadily increasing. The COVID-19 pandemic, and especially its consequences, increased public awareness to mental health needs [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mental health-related impact of the pandemic is not limited to those diagnosed with COVID-19. For example, a study of pandemic-related stressors and overall psychological distress found that nearly half of participants noted an increase in mild psychological distress regardless of COVID-19 infection, with distress prior to the pandemic, financial stressors, and work/life balance stressors all associated with higher distress during the pandemic [ 12 ]. However, evidence suggests that there is a prolonged mental health impact, including perceived stress, on individuals diagnosed with COVID-19 compared to healthy controls, with hypotheses that it is most pronounced 1–4 months after diagnosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Die COVID-19-Pandemie hat Angst, Leid und Stress in der Allgemeinbevölkerung ausgelöst. Insbesondere Maßnahmen zur Eindämmung von Übertragungswegen wie häusliche Isolation, Kontaktbeschränkungen, Homeoffice, Einschränkung sozialer Aktivitäten, zunächst social dann physical distancing haben dazu beigetragen, dass die physische und psychische Gesundheit vieler Menschen abgenommen hat und sich die Versorgung und somit auch Symptomatik von Patient:innen mit chronischen Erkrankungen, insbesondere psychischen Erkrankungen, verschlechtert hat [7,8,9]. Eine Studie aus Großbritannien zeigte, dass physical distancing zu erhöhtem Auftreten von Angst-und depressiven Erkrankungen in der Allgemeinbevölkerung führt [10].…”
Section: Introductionunclassified